Heat stroke: what goes on at vascular level? - Iftikhar, Abeer; Sohail, Hamza (International Journal Of Community Medicine And Public Health, 2020)
Heat stroke is the most calamitous consequence of environmental heat stress affecting every age group that can be traced back to more than 2000 years. It can be defined as a form of hyperthermia associated with a systemic inflammatory response leading to multiorgan dysfunction syndrome in which encephalopathy predominates. Based on its etiology, heat stroke can be divided into classic (resulting from exposure to high environmental temperatures) (called classic or non-exertional heat stroke) or exertional heat stroke (from strenuous exercise).